The relationship of p50 with clinical outcomes in ventilated preterm infants - Kaltsogianni, Ourania; Harris, Christopher; Nasikas, Stergios; Greenough, Anne; Dassios, Theodore (Frontiers in Pediatrics, 2025)
PurposeThe arterial oxygen tension at which haemoglobin is saturated at 50% (p50) can be used as a marker of respiratory disease severity. We aimed to explore whether p50 was higher in preterm infants who developed bronchopulmonary dysplasia (BPD) and extrapulmonary complications of prematurity compared to infants who did not.MethodsVentilated infants born before 32 weeks of gestation with central arterial access were retrospectively studied. The p50 was measured by automated blood gas analysis in the first three days after birth. Outcomes included BPD, intraventricular haemorrhage (IVH), retinopathy of prematurity (ROP) and necrotising enterocolitis (NEC).ResultsOne hundred and five infants (50 male) with a median (IQR) gestational age of 26.6 (24.9–28.6) weeks and birth weight of 0.88 (0.68–1.13) kg were studied. They had a median (IQR) p50 of 3.34 (3.08–3.77) kPa. IVH was significantly associated with the p50 (adjusted p = 0.020, Odds Ratio: 2.9, 95% CI: 1.2–7.1) after adjusting for gestational age. The p50 was not significantly different in infants who developed BPD, ROP and NEC vs. the infants who did not develop these complications after adjusting for confounders.ConclusionIntraventricular haemorrhage in ventilated preterm infants might be associated with an increased p50 in the early days after birth.